# Show that $(1+e^{ix})(1+e^{-ix}) = 2 + 2\cos x$ [closed]

Show that $$(1+e^{ix})(1+e^{-ix}) = 2 + 2\cos x$$

## closed as off-topic by Semiclassical, Stefan Mesken, Henrik, Davide Giraudo, SBareSDec 6 '16 at 0:04

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Semiclassical, Stefan Mesken, Henrik, Davide Giraudo, SBareS
If this question can be reworded to fit the rules in the help center, please edit the question.

• Just multiply it out and use Euler's formula. – copper.hat Dec 5 '16 at 19:49
• well e^i + 1 = 0, so i can kinda see where the two comes from, but i dont know about the 2cosx – Alex Robinson Dec 5 '16 at 19:49
• @copper.hat Please can you show me. I'm not too sure on how to use Euler's formula sorry. – Edward Burfield Dec 5 '16 at 19:50
• What do you mean? Euler's formula just says $e^{it} = \cos t +i \sin t$. Multiply the above and expand the remaining exponential terms with this formula and that will give the result. – copper.hat Dec 5 '16 at 19:51

$(1+e^{ix})(1+e^{-ix})=1+e^{-ix}+e^{ix}+1$

$=2+e^{-ix}+e^{ix}$ $=2+2\cfrac{e^{-ix}+e^{ix}}{2}$ $=2+2\cos(x)$

• Thank you very much that's perfect :) – Edward Burfield Dec 5 '16 at 19:52
• 2 minutes sorry wont let me – Edward Burfield Dec 5 '16 at 20:00

The Euler formula states that : $$e^{ix}=cos(x)+isin(x)$$ And : $$e^{-ix}=cos(x)-isin(x)$$ Also remember that : $$sin^2(x)+cos^2(x)=1$$

$$z \bar{z}=||z||^2$$

If $z=1+e^{ix}$ then $\bar{z}=1+e^{-ix}$

$$(1+e^{ix})(1+e^{-ix})=||1+e^{ix}||^2=(1+\cos{x})^2+\sin^2{x}=2+2\cos{x}$$